2012
DOI: 10.1146/annurev-nutr-071811-150713
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Cancer Survival

Abstract: Although obesity is a well known risk factor for several cancers, its role on cancer survival is poorly understood. We conducted a systematic literature review to assess the current evidence evaluating the impact of body adiposity on the prognosis of the three most common obesity-related cancers: prostate, colorectal, and breast. We included 33 studies of breast cancer, six studies of prostate cancer, and eight studies of colorectal cancer. We note that the evidence over-represents breast cancer survivorship r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
126
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 107 publications
(236 reference statements)
0
126
0
3
Order By: Relevance
“…This may have resulted in a variation in the body composition response to the exercise training and contributed to the nonsignificant effect of the intervention on this aspect of health-related physical fitness. Because of the potential association of poor body composition with negative disease and survival outcomes in CRC survivors (Parekh et al 2012), future research may consider interventions with larger samples with greater statistical power to detect body composition changes and allow for subgroup analyses; with a greater volume of exercise; that are longer in duration; and (or) that are combined with reduced caloric intake to maximize changes in body composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have resulted in a variation in the body composition response to the exercise training and contributed to the nonsignificant effect of the intervention on this aspect of health-related physical fitness. Because of the potential association of poor body composition with negative disease and survival outcomes in CRC survivors (Parekh et al 2012), future research may consider interventions with larger samples with greater statistical power to detect body composition changes and allow for subgroup analyses; with a greater volume of exercise; that are longer in duration; and (or) that are combined with reduced caloric intake to maximize changes in body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has also suggested that poor body composition (i.e., obese and overweight) negatively affects CRC recurrence and survival (Parekh et al 2012). Unfortunately, CRC survivors have the highest levels of inactivity (60%) among Canadian cancer survivors, and over half of these individuals are either overweight (39%) or obese (17%) (Courneya et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…American Cancer Society (ACS) estimates that 29% of all newly diagnosed malignant disease will be breast cancer and it will be cause in 16% of the deaths (Parekh et al, 2012;Siegel et al, 2012;Taghavi et al, 2012). Increased number of survivors after diagnosis of breast cancer suggests that modifiable risk factors that can improve remission, survival and quality of life should have to be investigated (Malcolm et al, 2009;Klimant et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2003; Parekh et al. 2012). While this association appears to be strong in postmenopausal women (Xia et al.…”
Section: Introductionmentioning
confidence: 99%